Makna Filosofis Upacara Tumpek Kandang Dan Keharmonisan Lingkungan Dalam Sistem Kosmos Di Desa Pakraman Sangkan Gunung Karangasem - I Gede Dopang Budiawan (Kamaya: Jurnal Ilmu Agama, 2018)
Tumpek Kandang is a pet sucking, in addition to the meaning of this ceremony is a form of praise of gratitude towards Ida Sang Hyang Widi Wasa because it has created binatantg that helps all the needs of human life, as well as meaningful to conserve animals and increase awareness of mankind to further improve affection for animals and their environment.